The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/bmjopen-2020-047753
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with peritraumatic stress symptoms among the frontline healthcare workers during the outbreak of COVID-19 in China

Abstract: ObjectivesThis study aimed to examine the prevalence of peritraumatic stress symptoms (PTSSs), perceived threat, social support and factors contributing to clinically significant PTSS among frontline COVID-19 healthcare workers (HCWs) in China.Design and settingAn online survey through self-administered questionnaires was conducted from 18 February to 4 March 2020, during the outbreak of COVID-19.Outcomes measuresPTSS was assessed using the post-traumatic stress disorder (PTSD) self-rating scale. Demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…According to a meta-review of systematic reviews, GAD and PTSD were the most prevalent COVID-19 pandemic-related mental health conditions affecting HCWs, especially nurses (8). Several more detailed studies, conducted after the first wave of the pandemic in China, reported that HCWs suffered from anxiety and stress-related symptoms, with prevalence ranging from 28.5 to 36.1% and 24 to 73.4%, respectively (9)(10)(11). In addition, some studies have reported high levels of anxiety and acute stress disorders in nurses more than a year after the start of the pandemic (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…According to a meta-review of systematic reviews, GAD and PTSD were the most prevalent COVID-19 pandemic-related mental health conditions affecting HCWs, especially nurses (8). Several more detailed studies, conducted after the first wave of the pandemic in China, reported that HCWs suffered from anxiety and stress-related symptoms, with prevalence ranging from 28.5 to 36.1% and 24 to 73.4%, respectively (9)(10)(11). In addition, some studies have reported high levels of anxiety and acute stress disorders in nurses more than a year after the start of the pandemic (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional studies have shown that healthcare workers experienced a considerable escalation in perceived stress as a result of the COVID-19 pandemic [ 4 , 5 , 6 ]. Results of a systematic review and meta-analysis of mental health problems during the early stages of the COVID-19 pandemic showed that approximately one in every three healthcare workers had experienced moderate–severe stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same review concluded that stress and sleep disturbances were the most common complaints among healthcare workers, accounting for 33% and 37%, respectively [ 7 ]. The commonly identified work stressors were: workflow disruptions, increased workloads, increased time constraints and fear of contracting or passing the infection to family members [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although implementing occasional mobility in this context is a likely cause of exhaustion, professional stress, and absenteeism, typically, these aspects have been largely ignored by necessity during the COVID-19 pandemic, to let emerge a new and flexible organization among departments and allow receiving patients in a massive and urgent manner [2]. The above-described situation gives rise to two phenomena that have not been addressed with equivalent level of attention: first, the comparison of frontline and second-line COVID-19 healthcare workers [3] has shown higher anxiety and depression levels [4] associated with deteriorated sleep quality and long-term post-traumatic stress in frontline workers [5]; second, the densification of adequate management of the mobility has deeply impacted the mission of human resources teams, with possible consequences on their health. Although managers are aware of mobility-associated drawbacks, they had to deal with both an increased workload and complicated decision making, which does not exempt them from occupational stress.…”
Section: Introductionmentioning
confidence: 99%